Community Perception of Medan City on Brand Medan Rumah Kita (Case Study of Medan Perjuangan Sub-District Community) - Akbar Aldi Kautsar; Ahmad Qorib; Abdul Rasyid (Budapest International Research and Critics Institute (BIRCI-Journal): Humanities and Social Sciences, 2020)
This study is entitled "Medan City Community Perceptions of the Brand Medan Rumah Kita", the purpose of this research is to find out the perception of the Medan Struggle community towards the Medan City government brand, to find out the existence of a community that supports the brand Medan Rumah Kita, to find out what media are used in container information and promotion of the Medan Rumah Kita brand. The theory used to analyze this research is communication theory. The object of research is the Medan City government office and Medan Perjuangan community. This research method is a case study approach method of Medan Perjuangan people and the population is the Head of Medan City Subdivision Government and Medan Perjuangan Subdistrict Community who have a Resident Identity Card (KTP) and have Social Media. The analysis technique used is domain analysis. The results showed that the majority of respondents gave the perception that Medan Rumah Kita whose name means our house must be taken care of, cared for properly if we stay at home in harmony with one of the Medan City government missions, namely cooperation in which together or working together build the Medan City together with the Medan City community, then the Medan Struggle community supports the Brand Medan Rumah Kita, and the Medan City Government has promoted the Medan Rumah Kita Brand through all mass media, electronic media, print media, online media, social media such as Facebook, Instagram, Twitter and YouTube.